Tobacco-related content on social networking sites: evidence from a youth-led campaign in India - Deepika Bahl; Shalini Bassi; Nishibha Thapliyal; Praveen Sinha; Monika Arora; Munish S. Gill (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Social networking sites (SNS) have become the contemporary platform of choice for advertising, promoting, sponsoring, boosting and expanding tobacco marketing. A youth-led campaign was conducted to (i) identify and collate violations of tobacco advertisement, promotion, and sponsorship on SNS; and (ii) undertake content analysis of the collated violations. # Methods After a series of capacity-building webinars aimed at empowering youths, they were tasked with collating posts (photos and videos) that showcased the promotion and sale of tobacco products online. Additionally, the youth identified relevant hashtags used to promote tobacco. # Results The youth identified 748 posts (photos and videos) on SNS where tobacco was being promoted. Most of these posts (84.7%) promoted the 'smoking form' of tobacco. Renowned celebrities and influencers with massive followership actively endorsed tobacco products. The youth identified 148 pages that were involved in selling tobacco online. Instagram (62.7%) accounted for the majority, followed by Facebook (23.7%). The most commonly available forms of tobacco in these online stores were 'smoked forms' (73.5%). In their efforts, the youth collated 1412 hashtags related to tobacco promotion. The most commonly reported hashtags were #smoking and #hookah. The maximum numbers of tobacco posts were for #vape (296 million) and #smoke (218 million). # Conclusions There is an urgent need to revise Section 5 of "*The Cigarettes and Other Tobacco Products (Prohibition of Advertisement and Regulation of Trade and Commerce, Production, Supply, and Distribution) Act, 2003*" to broaden the coverage of tobacco advertising, promotion, and sponsorship (TAPS) prohibition on all internet-based platforms including SNS to protect Indian youth.